October 1929, a walk in the sky - Pico Valimaña, Ramón (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
In the late twenties of the last century began to address a full and deliberate consideration of the territory from the height. Passed the fascination with the aircraft as an object and recomposed emotions after the initial contact with the air, begins the exploration, serene eyes emerge on land that has been down. In October 1929, Le Corbusier will have the opportunity to explore the fabulous American territory from above in a walk through the air during a peaceful southern spring that belongs him to discover the strong relation between site and architecture. Since then, accompanied throughout his sketchbook, would travel thousands of miles through the air: South America and M’zab, meanders and deserts, are, although not their first flights, the whole experience definitely transcendent in reshaping the spatial and geographic coordinates of an architect in love with aviation.
Keywords: Aviation; landscape; aerial gaze; Le Corbusier